2021
DOI: 10.1111/cas.15090
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein non–metastatic melanoma protein B functions with growth factor signaling to induce tumorigenesis through its serine phosphorylation

Abstract: The global incidence of breast cancer has been on the rise since the late 1970s. [1][2][3] Glycoprotein non-metastatic melanoma protein B (GPNMB), a type I transmembrane protein, is highly expressed in various cancers, including breast cancer. A high level of GPNMB expression is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…51 We have also reported that serine phosphorylation in the intracellular domain of GPNMB might be mediated by RTK pathways upon EGF or FGF-2 stimulation and be important for EMT and stemness genes' induction. 52 As mentioned above, FGFR3 activation is frequently found in bladder cancers. Therefore, it would be interesting to investigate the contribution of serine phosphorylation of GPNMB in acquisition of cellular motility in bladder cancers as well as those of the RGD motif and KLD.…”
Section: Discussionmentioning
confidence: 90%
“…51 We have also reported that serine phosphorylation in the intracellular domain of GPNMB might be mediated by RTK pathways upon EGF or FGF-2 stimulation and be important for EMT and stemness genes' induction. 52 As mentioned above, FGFR3 activation is frequently found in bladder cancers. Therefore, it would be interesting to investigate the contribution of serine phosphorylation of GPNMB in acquisition of cellular motility in bladder cancers as well as those of the RGD motif and KLD.…”
Section: Discussionmentioning
confidence: 90%
“…[5] GPNMB gene is located on chromosome 7q15 and is involved in cell proliferation, apoptosis and differentiation. [6,7] Studies have shown that GPNMB expression is up-regulated in head and neck squamous cell carcinoma, and its high expression is associated with poor prognosis. [8] Huang et al [9] found that GPNMB was an independent prognostic factor for triple negative breast cancer recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 24 , 25 , 26 We have previously demonstrated the importance of GPNMB in tumorigenic functions such as growth in vitro and in vivo, cellular migration and invasion, and induction of stem‐like properties in breast cancer cells. 27 , 28 , 29 , 30 Although the oncogenic role of this protein was reported in some cancer types, little is known about GPNMB involvement in progression of HNSCC, especially LSCC. Previously, it was reported that GPNMB promotes migration of oral SCC (OSCC) and invasion of HNSCC, 31 , 32 while the contributory effects on tumorigenic function in LSCC remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Glycoprotein NMB (GPNMB), a type 1 transmembrane protein reported to be involved in malignant progression of various cancers, such as melanoma, glioma, and triple‐negative breast cancer, may be such a target, as its high expression is thought to be a poor prognostic factor in those cancers 23–26 . We have previously demonstrated the importance of GPNMB in tumorigenic functions such as growth in vitro and in vivo, cellular migration and invasion, and induction of stem‐like properties in breast cancer cells 27–30 . Although the oncogenic role of this protein was reported in some cancer types, little is known about GPNMB involvement in progression of HNSCC, especially LSCC.…”
Section: Introductionmentioning
confidence: 99%